Pengaruh Kurs Rupiah Dan Right Issue Terhadap Harga Saham PT Telekomunikasi Indonesia Tbk Yang Listing Di Jakarta Islamic Index - Muhammad Fauzan (Universitas Islam Negeri Sumatera Utara, 2018)
This study discusses the effect of rupiah exchange rate and right issue on stock price of PT. Telekomunikasi Indonesia Tbk listing in Jakarta Islamic Index (JII). The purpose is to determine the effect between the rupiah exchange rate and the right issue against the stock price of PT. Telekomunikasi Indonesia Tbk and to find out which factors have the most influence on stock prices of PT. Telekomunikasi Indonesia Tbk. Data collection method uses time series secondary data obtained from the official website of Bank Indonesia and PT. Danareksa Sekuritas. The data collected are from January 2013 to December 2016. Multiple linear regression is used as an analytical technique. The results showed that the variables of the rupiah exchange rate against the Dollar and the right issue variable jointly affect the stock price of PT. Telekomunikasi Indonesia Tbk. From result of regression analysis known that right issue have stronger influence than rupiah exchange rate to share price of PT. Telekomunikasi Indonesia Tbk.